Student teachers' self-evaluation and perceived social evaluation of their future profession in South Tyrol - Italy - Barbara Gross (Pensa MultiMedia, 2019)
Focusing on the student teachers' evaluation of the prestige of their future profession is needed to include this aspect of the professionalization process in teacher education and training. Hence, knowledge on student teachers' perceptions is of fundamental worldwide relevance for universities to make the teaching profession more attractive to a wider pool of candidates. Research has shown that the teaching profession has a low social prestige, especially in the Mediterranean area, but there is no evidence on whether the perceived social prestige of the students' future profession coincides with the students' personal esteem of the profession. Therefore, this paper gives new insights in the self-evaluation and perceived external, social evaluation of the prestige of the teaching profession among student teachers in one Italian university (Free University of Bozen-Bolzano, N = 154). The results show that student teachers' self-evaluation and perceived external, social evaluation considerably and significantly diverge. Finally, implications for decision makers and university stakeholders will be discussed in this paper.